2018
DOI: 10.1136/bmjopen-2018-023587
|View full text |Cite
|
Sign up to set email alerts
|

Inpatients’ assessment of outcome at psychiatric institutions: an analysis of predictors following a national cross-sectional survey in Norway

Abstract: ObjectivesThe objective was to assess the importance of different types of predictors for patient-reported outcome, both background factors at the patient level and healthcare predictors related to structure and processes of healthcare.DesignCross-sectional patient experience survey.SettingAll 280 secondary care institutions in Norway providing inpatient care for adult psychiatric patients.Participants1683 inpatients responded to the questionnaire on-site (73.4%).Primary outcome measuresThe outcome scale of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Another previous national study using the PIPEQ-OS assessed the importance of different types of patientreported predictors for outcome assessments for mental health inpatients. The results indicated that the most important structure and process variables for patient outcome assessments were related to patientcentred interactions [19].…”
Section: Discussionmentioning
confidence: 99%
“…Another previous national study using the PIPEQ-OS assessed the importance of different types of patientreported predictors for outcome assessments for mental health inpatients. The results indicated that the most important structure and process variables for patient outcome assessments were related to patientcentred interactions [19].…”
Section: Discussionmentioning
confidence: 99%
“…Another previous national study using the PIPEQ-OS assessed the importance of different types of patient-reported predictors for outcome assessments for mental health inpatients. The results indicated that the most important structure and process variables for patient outcome assessments were related to patient-centred interactions [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…using three main diagnosis categories) or unaccounted confounding from, e.g. socioeconomic status [ 28 ]. However, adjustment for patient age, sex and main diagnosis had no substantial influence on the unadjusted point estimates indicating that confounding from these factors has only minor influence on the results.…”
Section: Discussionmentioning
confidence: 99%